2017
DOI: 10.1097/pp9.0000000000000010
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Health Outcomes Examined in Randomized Controlled Trials Using Guided Imagery

Abstract: Introduction Guided imagery involves the controlled visualization of detailed mental images. This integrative health technique is used for healing, health maintenance, or the treatment of specific conditions. Guided imagery is an integral part of mindfulness meditation, hypnosis, and various relaxation exercises. However, evidence to support the widespread use and dissemination of guided imagery interventions has been lacking. The purposes of this scoping review were to document the scope of health outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Mental imagery has been used to improve athletic skills and motivation and to help visualize physical activity‐related goal achievements (Martin, Moritz, & Hall, 1999). Mental imagery interventions have been used in several health‐related contexts, with the majority showing beneficial results (Giacobbi et al., 2017), including for physical activity (Conroy & Hagger, 2018). (Chan & Cameron, 2012) reported that self‐regulation interventions that incorporated approach imagery (i.e., attaining goals or behaviour) and process imagery (i.e., the steps one takes to achieve goals or behaviour) increased physical activity and cognitions over 4 weeks compared with interventions that included only process or neutral imagery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental imagery has been used to improve athletic skills and motivation and to help visualize physical activity‐related goal achievements (Martin, Moritz, & Hall, 1999). Mental imagery interventions have been used in several health‐related contexts, with the majority showing beneficial results (Giacobbi et al., 2017), including for physical activity (Conroy & Hagger, 2018). (Chan & Cameron, 2012) reported that self‐regulation interventions that incorporated approach imagery (i.e., attaining goals or behaviour) and process imagery (i.e., the steps one takes to achieve goals or behaviour) increased physical activity and cognitions over 4 weeks compared with interventions that included only process or neutral imagery.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these promising findings, mental imagery studies represent a small proportion of behaviour change interventions (Conroy & Hagger, 2018; Giacobbi et al., 2017), and even fewer mental imagery‐based health behaviour change studies have also incorporated elements of self‐regulation theory (Chan & Cameron, 2012; Loft & Cameron, 2013). In addition, existing interventions are time‐intensive and may represent a major barrier to eventual uptake of interventions in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…One self‐management tool with evidence to support its use to address physical activity, food cravings, and mental health challenges is guided imagery 14–16 . Guided imagery is a quasiperceptual, multisensory, conscious experience that resembles the actual perception of some object or scene in the absence of external stimuli 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Guided imagery is used to increase an individual's preparation and motivation toward a task, behavior, or health goal 14 . This cognitive technique has been used widely 16 but has not been tested with pregnant women as part of a multiple health behavior change intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a popular exercise in meditation and stress prevention is to imagine a "safe" place (Giacobbi et al, 2017). A sense of belonging or feeling "home" could thus be a feeling inside the person that can also be carried into other contexts.…”
Section: Introductionmentioning
confidence: 99%